MENANAMKAN KARAKTER DISIPLIN SISWA DALAM PERSPEKTIF PENDIDIKAN AGAMA ISLAM - Najmuddin, Muhammad Syafiq (IAIIG Cilacap, 2018)
All Educators were certainly crave an atmosphere of discipline in every learning process with their students. But apparently, to create discipline was not easy and not enough just with words. The behavior of the students was the responsibility of an educator, the good and bad of students will be reflected in who teached, where and how he learned. The discipline plan as a discipline strategy for children that can be applied in accordance with the perspective of Islamic Religion Education is 10. First, Give Appreciation to them when they are doing good. Second, using positive signals. Third, using physical closeness. Fourth, using questions to get the child back focused. Fifth, maintain personally. Sixth, Recognize and redirect. Seventh, provides a clear reminder of the rules. Eighth, provide clear choices. Ninth, Using agreed consequences. Tenth, using an exit strategy. Keyword: Discipline, Islamic Religion Education